Hemostasis and female sex hormones - О. А. Ефименко; И. А. Родионова (Publishing House TRILIST, 2018)
The review considers modern concepts of the pathogenesis of coagulation disorders in women and the participation of endogenous and exogenous sex steroids in it. The analysis of the results of studies in recent years demonstrates significant contradictions on the influence of endogenous female sex steroids on the development of thrombotic events. In the context of thromboembolic complications association with the use of modern hormone containing medications, in particular combined hormonal contraceptives, genetically determined thrombophilia appears to be essential, but the possibility of their routine diagnostics to reduce risks is still not fully defined. To date, recent clinical studies support the early use of menopausal hormone therapy (MHT) to slow the rate of atherosclerosis development and primary prevention of cardiovascular disease in women in early menopause. At the same time, researchers put forward a temporary theory of the use of MHT (the early beginning of the use of MHT from the onset of menopause provides the best protective effect of hormones on the vascular wall) as a way of successful prevention of cardiovascular diseases. Correctly chosen tactics of preventive measures for a specific gynecologic patient can significantly reduce the risk of thromboembolic complications, prevent the development of disseminated intravascular coagulation syndrome or at least reduce its severity, shorten treatment time, and reduce morbidity and mortality caused by this pathology. Strict individual approach and targeted prevention, if it is carried out in all medical institutions and at all stages of management of pregnant and gynecological patients, can significantly reduce the frequency of these formidable complications.